A novel 125I seeds fixed on gastric tube for treatment of inoperable esophageal carcinoma: A case report. Issue 14 (9th April 2021) - Jin, Jing; Yu, Yang; Jia, Weikun; Li, Wei
Abstract : Abstract: To explore the treatment benefit of 125I seeds fixed on a gastric tube in the early inoperable esophageal carcinoma (EC). Three senile patients with early inoperable EC who were treated with brachytherapy between October 2017 and February 2019 were included in this study. 125I seeds were fixed on the gastric tube, which was then inserted on the surface of the EC. One patient suffered from severe pulmonary insufficiency; 1 patient underwent colon cancer surgery one week before treatment and suffered from liver dysfunction and esophageal varices; 1 patient suffered from venous embolism of lower extremities and pulmonary artery embolism. All three patients were successfully operated and completed treatment. During the operation, no displacement and shedding of 125I seed gastric tube occurred. After surgery, the discomfort while swallowing and pain after eating were significantly improved. Moreover, dysphagia was relieved in patient 3. In addition, no complications, such as perforation or bleeding, occurred. Local lesions were effectively controlled. Gastric tube with 125I seeds provides a new treatment protocol for inoperable EC and malignant obstruction of esophageal carcinoma.